Wastewater Treatment, Plant Dynamics and Management in Constructed and Natural Wetlands - Vymazal, Jan (Springer Netherlands : Imprint: Springer, 2008)
Wetlands were historically neglected until it was revealed that they could be economically valuable to man. They are one of the most dynamic ecosystems in the world and have many functions for society. For example, natural wetlands provide food staples, building materials, irrigation of agricultural lands, waterways, shelter for wildlife, and a means of flood control. Constructed wetlands provide a reliable treatment technology for various types of polluted water, including industrial and agricultural wastewater, stormwater runoff, municipal sewage and landfill leachate. Both natural and constructed wetlands require careful management in order to optimally provide these functions, and this volume presents the latest results in the field of management and performance optimization of these systems. The book covers wetland science worldwide, with examples from Europe, North and South America, Asia and Africa. It will be of interest not only to ecological and environmental scientists and teachers, but also to engineers, regulators and landscape planners.